2008
DOI: 10.1086/592205
|View full text |Cite
|
Sign up to set email alerts
|

Education and Cognitive Ability as Direct, Mediating, or Spurious Influences on Female Age at First Birth: Behavior Genetic Models Fit to Danish Twin Data

Abstract: The authors study education and cognitive ability as predictors of female age at first birth (AFB), using monozygotic and dizygotic female twin pairs from the Middle-Aged Danish Twin survey. Using mediated regression, they replicate findings linking education (and not cognitive ability) to AFB. But in a behavior genetic model, both relationships are absorbed within a latent variable measuring the shared family environment. Two interpretations are relevant. First, variance in AFB emerges from differences betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
88
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(102 citation statements)
references
References 65 publications
10
88
4
Order By: Relevance
“…First, Rodgers et al (2008) used Danish twin data, and found that the link from education/cognitive ability to maternal age at first birth (AFB) was entirely accounted for by between-family variance: "variance in AFB emerges from [IQ and education] differences between families, not differences between sisters within the same family" (Rodgers et al, 2008, p. 202). We have exactly the same type of result in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…First, Rodgers et al (2008) used Danish twin data, and found that the link from education/cognitive ability to maternal age at first birth (AFB) was entirely accounted for by between-family variance: "variance in AFB emerges from [IQ and education] differences between families, not differences between sisters within the same family" (Rodgers et al, 2008, p. 202). We have exactly the same type of result in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…1). However, the AFB turns out to be a challenge to study, since other studies in the U.S. (Neiss et al 2002) and Denmark (Rodgers et al 2008) show no significant effect on the AFB of women.…”
Section: Heritability Of Afbmentioning
confidence: 95%
“…Opposed to the commonplace practice of including right-censored cases in demography and sociology (e.g., Mills 2011), it is uncommon to deal with censored information in genetic studies and childless women are generally excluded from the sample Neiss et al 2002;Nisén et al 2013;Rodgers et al 2008). Using data from the TwinsUK, Tropf et al (2015a) empirically examined whether the inclusion of censored information in a Tobit model affects heritability estimates compared to the classic models.…”
Section: Heritability Of Afbmentioning
confidence: 99%
“…Still, studies of monozygotic twins represent an important way of identifying the effects of education after controlling for genetic influences. Several twin studies have found a strong positive effect of education on, for instance, mental health (Haworth et al 2008;Rodgers et al 2008). …”
Section: Effects Of Education On Health and Mortalitymentioning
confidence: 99%